The effect of thermal cycling by electron-beam surfacing on structure and wear resistance of deposited M2 steel; Applied Surface Science; Vol. 263 - Gnyusov S. F. Sergey Fedorovich; Ignatov A. A.; Durakov V. G.; Tarasov S. Yu. (2012, 2012)
Title screen